Threatened Selves and Differential Prejudice Expression by White and Black Perceivers - Shapiro, Jenessa R. (2010)
Previous theorizing suggests that often-stigmatized individuals may be just as likely, if not more likely, than infrequently stigmatized individuals to protect self-regard by derogating members of low-status groups after receiving negative feedback from high-status others. Often-stigmatized individuals, however, can discount criticism from these high-status others as reflecting prejudice, thereby making outgroup derogation unnecessary as an esteem-protective strategy. Replicating past research, White participants in Experiment 1 expressed prejudices after receiving negative feedback from a White evaluator; as predicted, however, Black participants did not. In Experiment 2, participants instead received negative feedback from Black evaluators (evaluators more likely to threaten Black participants’ self-regard). Here, contrary to previous theorizing, Black participants expressed prejudices, not toward another low-status group, but toward high-status Whites. In all, findings reveal flaws in previous assumptions that frequently stigmatized individuals may be especially prone to devalue lower-status others after rejection or negative feedback from members of higher-status groups.